Peran Guru Kristen dalam Membentuk Pemahaman Siswa tentang Penciptaan Alam Semesta yang Bersumber pada Alkitab - Fernando Christofer; Wahyu Irawati (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The fall of man into sin has made man fail to understand God's truth about creation of the universe. Humans seek to uncover the truth of creation with secularism, which focuses on their thought and rejects God as creator. Worldview of creation that opposes God as Creator has become philosophical issues in Christian education that must be criticized with Biblical truth. Christian teachers have responsibility to shape students' worldview based on the Bible. This paper has purpose to examine Christian teachers’ role in shaping students' worldview of creation of the universe based on Biblical truth. The study was conducted with a study literature method that discusses three focuses named students’ worldview of creation of the universe, the role of Christian teachers in education, and the role of Christian teachers in shaping students' worldview. The worldview is formed from doctrine of Biblical creation. The role of the Christian teacher in shaping students' worldview is the responsibility of guiding and directing students learning orderliness of the universe which is by God’s work in Biblical truth. The next research suggested to carry out further analysis of students' perceptions and responses the understanding of creation as a form of evaluation of Christian teacher teaching practices.